PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Rina, Elvina; Febriana, Rina; sovia, Anny (Pendidikan Matematika, 2014)
ABSTRACTThe research based on the lack of problem about students are less holding responsible in doing given and studentsâ comprehensionâs mathematical concept. This research had a purpose to know that studentsâ comprehension mathematical concept in which the learning model applied was Technique Business of Berisiko, better than studentsâ comprehension in was conventional learning at grade VIII of SMPN 2 Lembah Melintang. Type of this research was experimental by research with random research design on the subject. Data analysis was done by using t-test with MINITABâs software. Result of hypothesis testing, the researcher got p-value = 0,033 < , thus the hypothesis of this research was accepted. There can be concluded that studentsâ comprehension mathematical concept in which the teaching model applied was technique business of Berisiko, was better than studentsâ comprehension of mathematical concept in which the applied was by conventional learning at grade VIII of SMPN 2 Lembah Melintang.